2021
DOI: 10.1155/2021/6665918
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of miR‐138 Increases Sensitivity to Cisplatin in Hepatocellular Carcinoma by Regulating EZH2

Abstract: Chemotherapeutic insensitivity is a major obstacle for effective treatment of hepatocellular carcinoma (HCC). Recently, new evidence showed that microRNAs (miRNAs) are closely related to drug sensitivity. This study aimed to investigate the relationship between miR-138 expression and cisplatin sensitivity of HCC cells by regulation of EZH2. CCK-8, EdU, and western blotting are determining the cell viability, proliferation, EZH2, and EMT-related protein expression. It was found that compared with normal samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…It has been reported that EMT induction can lead to cisplatin resistance [ 182 ]. MiRNA-138 reduces EZH2 expression to inhibit EMT, resulting in an increase in cisplatin sensitivity in hepatocellular carcinoma cells [ 183 ]. Overall, these studies agree with the fact that miRNA/EZH2 axis can affect proliferation, metastasis, and therapy response of hepatocellular carcinoma cells, and in this way, different molecular pathways such as Wnt, STAT3 and EMT are affected.…”
Section: Non-coding Rnas and Ezh2 Signalingmentioning
confidence: 99%
“…It has been reported that EMT induction can lead to cisplatin resistance [ 182 ]. MiRNA-138 reduces EZH2 expression to inhibit EMT, resulting in an increase in cisplatin sensitivity in hepatocellular carcinoma cells [ 183 ]. Overall, these studies agree with the fact that miRNA/EZH2 axis can affect proliferation, metastasis, and therapy response of hepatocellular carcinoma cells, and in this way, different molecular pathways such as Wnt, STAT3 and EMT are affected.…”
Section: Non-coding Rnas and Ezh2 Signalingmentioning
confidence: 99%
“…Furthermore, miR-651-3p can inhibit ATG3 [ 76 ] mediated cell autophagy to strengthen the susceptibility of HCC to cisplatin resistance [ 77 ]. Studies have revealed that miR-138-5p inhibits EZH2 and intensifies the sensitivity of HCC to cisplatin [ 78 ]. Likewise, the overexpression of miR-9 in HCC increases their sensitivity to cisplatin by preventing EMT and inhibiting EIF5A2.…”
Section: Mirnas and Systemic Treatment Resistancementioning
confidence: 99%
“…Cisplatin resistance: Cisplatin is one of the few most common chemotherapy drugs used to treat HCC. However, thus far, the drug resistance of HCC cells during chemotherapy has been revealed to be the main factor affecting chemotherapy failure[ 110 , 111 ]. Therefore, how to control the occurrence of cisplatin resistance in HCC cells and improve drug sensitivity and therapeutic effects are critical to prolonging the survival of patients with advanced HCC.…”
Section: Role Of Circrnas In Hccmentioning
confidence: 99%